Workshop Google Classroom sebagai Media Pembelajaran Daring di SD Negeri Gollu Sapi - Gergorius Kopong Pati; Karolus Wulla Rato (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The development of digital technology and the impact of the pandemic have shifted the learning paradigm in elementary schools from traditional face-to-face models to technology-based online systems. However, the limited mastery of teachers in utilizing digital learning media, particularly Google Classroom, has become a major obstacle in implementing effective online learning. This community service activity aims to improve the competence of teachers at SD Negeri Gollu Sapi in managing technology-based learning through the use of Google Classroom. The implementation method consists of four stages: preparation, workshop implementation, practice mentoring, and evaluation. The workshop was designed interactively by combining material presentation, demonstration, discussion, and hands-on practice, covering the creation of virtual classes, uploading teaching materials, assigning tasks, and conducting online assessments. The results of the activity showed a significant improvement in teachers’ skills, both in independently managing online classes and in applying the main functions of Google Classroom. Teachers were able to create digital teaching materials, set assignment schedules, provide feedback, and prepare technology-based assessments. In addition, this activity also produced an online article publication and video documentation as additional outputs. The teachers’ enthusiasm during the implementation indicates that this activity is useful and relevant to the needs of 21st-century learning. With this training, teachers are expected to become more adaptive to the digital transformation in education, thereby supporting the achievement of a more interactive, effective, and sustainable learning process in the digital era.